Consensus statement on neurorehabilitation during COVID-19 times: Expert group on behalf of the Indian Federation of Neurorehabilitation (IFNR) - Rajinder K Dhamija; Abhishek Srivastava; Sonal Chauhan; Urvashi Shah; Taral Nagda; Deepak Palande; Sonal Chitnis; P S Dantala; John M Solomon; S Murali Krishnan; Hitav Someshwar; Nirmal Surya (Annals of Indian Academy of Neurology, 2021)
The COVID19 pandemic in India is causing significant morbidity and disruptions of healthcare delivery. The rapidly escalating contagion is straining our public health system, which is already under pressure due to a shortage of infrastructure and inadequate workforce. Neuro rehabilitation services that are still in its infancy in our country have been significantly interrupted in the last six months. An expert group from Indian Federation of Neurorehabilitation (IFNR) have formulated the guidelines and consensus recommendations for Neurologists, Physiatrists, and Therapists managing neurological disabilities during COVID 19. The aim of this consensus paper is to sensitize the clinicians and therapists about maintaining the continuum of care and rehabilitation needs of Covid patients as well as non Covid patients with neurological disorders during the ongoing COVID 19 pandemic